Seminar in delavnica 'Tujejezično učbeniško gradivo in aplikacija na slovenščino' - Markovič, Andreja (Jezik in slovstvo, 1997)
The article is an analysis of a selection of foreign language textsbooks carried out in the academic year 1995/96 by the Slovene language teachers for the Year-Long Course of Slovene at the Centre for the Slovene Language as a Second/Foreign Language. The analysis was presented at the seminar for continuing education of teachers of Slovene as a Foreign language in November 1995. A part of the seminar was also a workshop in which the particioants designed samples of textbook materials for teaching and learning Slovene as a foreign language
Keywords: Slovene; slovenščina; slovenščina kot drugi ali tuji jezik; učbeniki; metodika; pouk